Modelagem matemática e a calculadora gráfica geogebra no estudo da função afim - Freire, José Rilke Leite (2021)
This work aims to analyze the teaching of Afim Function from alternative methodologies that enable an improvement in student learning, also aiming at an optimization of results in external educational evaluations. For the research, we used a theoretical framework focused on aspects related to teacher education, new trends in Mathematics teaching, as well as the use of educational software in classrooms. For this purpose, a workshop was applied and presented in three stages. In the first stage, problem-situations were elaborated in which Mathematical Modeling is present as a methodological proposal and student performance was analyzed using the descriptors of SIMAIS (Integrated Institutional Monitoring and Evaluation System). In the second part of the workshop, the content was worked on from the textbook, making parallels with the items covered in the initial part. In the last step, an activity was developed with the GeoGebra Graphical Calculator application to observe the contributions that the use of mathematical software can bring to the teaching-learning process of the subject. After applying the three stages of the workshop, a report was made on how it was developed, as well as a qualitative analysis of the results achieved by the students in solving the proposed problems, comparing performance with the skills sought in each activity